How well do elderly people cope with uncertainty in a learning task? - Chasseigne, Gérard; Grau, Sébastien; Mullet, Etienne; Cama, Vincent (Acta psychologica, 1999)
The relation between age, task complexity and learning performance in a Multiple Cue Probability Learning task was studied by systematically varying the level of uncertainty present in the task, keeping constant the direction of relationships. Four age groups were constituted: young adults (mean age=21), middle-aged adults (45), elderly people (69) and very elderly people (81). Five uncertainty levels were considered: predictability=0.96, 0.80, 0.64, 0.48, and 0.32. All relationships involved were direct ones. A strong effect of uncertainty on `control', a measure of the subject’s consistency with respect to a linear model, was found. This effect was essentially a linear one. To each decrement in predictability of the task corresponded an equal decrement in participants' level of control. This level of decrement was the same, regardless of the age of the participant. It can be concluded that elderly people cope with uncertainty in probability learning tasks as well as young adults.